Wednesday

October 1, 2014

October 1, 2014

Posted by **Megan** on Tuesday, September 17, 2013 at 9:27pm.

- elementary functions -
**Reiny**, Tuesday, September 17, 2013 at 9:34pmf(x+h) = (x+h)^2 + x+h - 3

= x^2 + 2xh + h^2 + x + h - 3

then ( f(x+h) - f(x) )/h

= (x^2 + 2xh + h^2 + x +h - 3 - x^2 - x + 3)/h

= ( 2xh + h^2 +h)/h

= h(2x + h + 1)/h

= 2x + h + 1 , h ≠0

**Answer this Question**

**Related Questions**

Calculus - Find the sum and difference functions f + g and f – g for the ...

calculus - let f(x) = (x)^(1/2) Compute the difference quotient for f(x)at a=37 ...

Pre-Calculus - Operations with Functions write the function below as either a ...

math 191 - Compute the difference quotient: [(f(x)- f(a))/(x-a)].. for f(x)= (-1...

Precalulus-NEED HELP! - PLEASE HELP! Compute the difference quotient: [(f(x)- f(...

Algebra - My problem is compute and simplify the difference quotient f(x+h)-f(x...

Pre-Calculus - Using the difference quotient to find M-sec for h=0.5 at x=1. f(...

Pre-Calculus - Using the difference quotient find M-sec for h=0.5 at x=1. f(x)=...

Math-Help asap please~ - For each function, the point given is the maximum or ...

programming - I need a help regarding this. Compute and display the sum o 1st ...